(untitled) (World Bulletin of Social Sciences, 2022)
The article discusses the development of the enlightenment movement in Central Asia, the development of socio-philosophical knowledge of people of mature human qualities who shared their knowledge of education in the region, as well as the famous children of Samarkand in the 20th century - Said Riza Alizoda and Saidahmad Hasankhoja’s son Siddiqi - Ajzi outlined their views on the social and economic, ideological, spiritual and moral foundations